Retraction: Selective Cerebro‐Myocardial Perfusion Under Mild Hypothermia During Primary Repair for Aortic Coarctation With Ventricular Septal Defect. Issue 4 (2nd November 2012) - Chen, Huiwen; Hong, Haifa; Zhu, Zhongqun; Liu, Jinfen
Abstract The following article from Artificial Organs, "Selective Cerebro‐Myocardial Perfusion Under Mild Hypothermia During Primary Repair for Aortic Coarctation With Ventricular Septal Defect" by Huiwen Chen, Haifa Hong, Zhongqun Zhu and Jinfen Liu, published online on 2 November 2012 in Wiley Online Library (wileyonlinelibrary.com), has been retracted by agreement between the authors, the journal Editor‐in‐Chief, Paul S. Malchesky, the International Center for Artificial Organs and Transplantation and Wiley Periodicals, Inc. The retraction has been agreed due to simultaneous publication of a substantially similar article, "Continuous Cerebral and Myocardial Perfusion During One‐Stage Repair for Aortic Coarctation With Ventricular Septal Defect", by Huiwen Chen, Haifa Hong, Zhongqun Zhu and Jinfen Liu, in Pediatric Cardiology 7 November 2012 [Epub ahead of print]. Controversy still exists on the use of deep hypothermic circulatory arrest (DHCA) and selective antegrade cerebral perfusion (SACP) on postoperative recovery. Selective cerebro‐myocardial perfusion (SCMP) has been described in neonatal and infant arch surgery. We therefore report outcomes of patients undergoing SCMP under mild hypothermia compared with DHCA and SACP. One hundred ten consecutive patients undergoing anatomic reconstruction of coarctation of the aorta (CoA) with ventricular septal defect (VSD) closure between January 1999 and July 2011 were retrospectively reviewed. Patients repaired under continuous cerebral and myocardial perfusion technique with mild hypothermia (32°C) (group A, n = 60) were compared with those repaired under DHCA (18°C) and SACP (group B, n = 50). In group A, single arterial cannula perfusion technique was used in 45 (75%) patients, and dual arterial cannula perfusion technique was used in 15 (25%) patients. Preoperative data were similar in both groups. There were no hospital mortalities in group A compared with two (4%) in group B. Compared with group B, group A had shorter myocardial ischemic time and cardiopulmonary time, fewer delayed sternal closures, shorter time to extubation, lower postoperative lactate levels, and fewer patients with low cardiac output requiring extracorporeal membrane oxygenation or multiorgan failure. During the postoperative course, there were no clinical or electrical neurologic events in either group. The mean length of follow‐up for group A was 5.2 ± 3.2 years, and for group B, it was 7.5 ± 3.1 years (P = 0.048). There was one late death in group B. There was no late death in group A. The actuarial survival for the two groups was similar (100% for group A vs. 96% for group B, P = 0.264). The freedom from all types of cardiac reintervention was 96.7% in group A and 89.6% in group B (P = 0.688). All patients were free from neurologic symptoms. Our perfusion strategy using continuous SCMP with mild hypothermia for CoA with VSD repair is feasible, is safe, was associated with improved postoperative recovery, and should be considered as one of the choices.